Spermatozoa Isolation and ABO H Group Typing with Proteinase K on Semen Contaminated Vaginal Material - Karagöz, Sema Demirçin; Ege, Beyhan (The Bulletin of Legal Medicine, 1997)
Physical and gynecological examinations and detection of spermatozoa in vaginal material are the procedures used to prove the sexual crimes as rape, sexual assault, sodomy and adultary cases. Besides these examinations, assessment of genetic markers in the vaginal material is necessary to identify the offender in cases of sexual assault with unknown perpetrator. In this study, the applicability of an absorbtion elution technique with proteinase K treatment is investigated to increase the reliability of ABO(H) group typing on semen contaminated vaginal swabs. It was seen that after Proteinase K treatment only spermatozoa remain in vaginal material and blood group obtained in conclusive reflects only the antigenic structure of spermatooza. It was calculated that ratio of obtaining a true result was 82.67 % with Proteinase K treated samples and 86 % with nontreated samples.Key Words : ABO(H) typing, vaginal material, sexual assault, proteinase K, spermatozoa.
Keywords: ABO (H) typing; vaginal material; sexual assault; proteinase k; spermatozoa